Evaluating a sensitive issue: reliability of a clinical evaluation for allodynia severity. (2nd January 2020) - Packham, Tara L.; Spicher, Claude J.; MacDermid, Joy C.; Quintal, Isabelle; Buckley, Norman
Abstract: Purpose/Aim: Allodynia is a common feature of neuropathic pain with few validated clinical evaluation options. We identified a need to estimate the measurement properties of the standardised evaluation procedure for static mechanical allodynia severity popularised by the somatosensory rehabilitation of pain method, known as the rainbow pain scale. This study (www.clinicaltrials.gov . NCT02070367) undertook preliminary investigation of the inter-rater and test-retest reliability of the rainbow pain scale. Methods: Persons with pain in one upper extremity after Complex Regional Pain Syndrome, a peripheral nerve injury or a recent hand fracture were recruited for assessment of static mechanical allodynia threshold using calibrated monofilaments by two raters at baseline, and repeated assessment one week later. Results: Single measures estimates suggested inter-rater reliability was substantial for the rainbow pain scale [intra-class correlation coefficient = 0.78 ( n  = 31), p  < 0.001]. Test-retest reliability was also excellent at with an intraclass correlation coefficient of 0.87 [ n  = 28, p  < 0.001]. However, confidence intervals suggest the true values could be more moderate, with lower bounds of the 95% confidence interval at 0.60 and 0.74, respectively. Conclusions: This pilot study has generated preliminary support for the inter-rater and test-retest reliability of the rainbow pain scale. Future studies should seek to increase confidence in estimates of reliability, and estimate validity and responsiveness to change in persons with somatosensory disorders.